PENGARUH SPIRITUAL LEADERSHIP TERHADAP DISIPLIN KERJA PERAWAT DI RUMAH SAKIT IBU DAN ANAK AISYIYAH SAMARINDA - Enok Sureskiarti; Vina Avioleta (Jurnal Surya Muda, 2019)
Discipline is a condition or respect that is in the employee's own rules and regulations. While work is the act of doing something that aims to get results. Thus, if the rules or provisions in the company are ignored or often violated, then the employee has a poor work discipline. Conversely, if the employee is subject to the provisions of the company, it describes the existence of a good discipline condition. One that is related to the effectiveness of a leadership in the workplace is inseparable from spiritual values. Spiritual leadership is leadership that brings worldliness to the dimension of divinity (spiritual). To find out the influence of spiritual leadership on nurses' work discipline at RSIA Aisyiyah Samarinda. This type of research is Quasi Experiment with Pretest-Posttest Desigen with control group. The population of this study were 22 respondents. Analysis includes univariate and bivariate analysis using paired t-test correlation and independent t-test. The results of the bivariate analysis of the Pairred T-Test correlation obtained the results of p-value = 0.005 <0.05, and for the results of 0.007 <0.05. From the results of the study it can be concluded that there is an influence of spiritual leadership on nurse work discipline